A comparative assessment of artificial and natural energy drinks in the epididymal and testicular milieu - Oluwakemi T. OYELOWO; Oluwapelumi I. AWOSIKA; Taiwo H. ADESINA (Studia Universitatis Babeș-Bolyai. Biologia)
Artificial and natural energy drinks are both taken for increased energy, physical stamina, and alertness, although they differ in composition. This study investigated the effects of artificial and natural energy drinks on the testicular milieu in male pubertal rats. Eighteen Wistar rats were randomly divided into 3 groups of 6 rats each and all animals had access to food ad libitum. Group 1: (control) received water only; Group 2: (artificial energy drink- AED) received AED; Group 3: (natural energy drink- NED) received NED. A dose of 1.41ml/day/150g animal was administered and this lasted for 28 days. Sperm and testicular variables, biochemical parameters, and hormonal assays were carried out. There were significant decreases in the levels of testosterone, Lactate dehydrogenase, glucose, 3β-Hydroxysteroid dehydrogenase, and 17β- Hydroxysteroid dehydrogenase activities in AED and NED groups when compared to the control group. There was a marked increment in sperm abnormalities in the NED group when compared to AED and control groups. Also, the intake of AED led to an elevated level of Glucose-6-phosphate dehydrogenase compared to the control while a significant reduction was observed in the NED group when compared to the AED group. Artificial and natural energy drinks although consumed for strength and vigor distorted epididymis and testicular integrity via alteration of the testicular metabolism, lowering sperm quality and androgenic hormones in pubertal male Wistar rats.